2020
DOI: 10.1016/j.apsusc.2020.146991
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the photocatalysts on ZrO2: An effective way to enhance the photocatalytic activity of SrSnO3

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 69 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…These results contrast with the work of Xuet al [ 54 ], who observed that the activity of the holes to generate oxidative species was less efficient in the IBU photodegradation mechanism. In the presence of Ag + ions, the photocatalysis had the smallest decrease in total degradation, possibly due tothe deposition of Ag 0 on the surface allowing better photocatalytic activity through the capture of photogenerated electrons avoiding recombination [ 32 , 62 ]. Overall, the order of photochemical activity in the photodegradation of IBU follows the order h + > ● OH > e − .…”
Section: Resultsmentioning
confidence: 99%
“…These results contrast with the work of Xuet al [ 54 ], who observed that the activity of the holes to generate oxidative species was less efficient in the IBU photodegradation mechanism. In the presence of Ag + ions, the photocatalysis had the smallest decrease in total degradation, possibly due tothe deposition of Ag 0 on the surface allowing better photocatalytic activity through the capture of photogenerated electrons avoiding recombination [ 32 , 62 ]. Overall, the order of photochemical activity in the photodegradation of IBU follows the order h + > ● OH > e − .…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the catalyst loading and dye concentration played a crucial role in the photocatalytic efficiency. Due to the octahedral tilting in the crystalline network of SnO 6 , this distortion plays an important role in the migration of photogenerated charge carriers in SrSnO 3 , CaSnO 3 , and BaSnO 3 for photocatalytic degradation of pollutants (Honorio et al, 2020). Honorio et al (2020) synthesized SrSnO 3 with ZrO 2 as a supporting semiconductor for photocatalytic degradation of a textile azo dye pollutant.…”
Section: Tantalum and Other Perovskite-based Materials In Photocatalysismentioning
confidence: 99%
“…Due to the octahedral tilting in the crystalline network of SnO 6 , this distortion plays an important role in the migration of photogenerated charge carriers in SrSnO 3 , CaSnO 3 , and BaSnO 3 for photocatalytic degradation of pollutants (Honorio et al, 2020). Honorio et al (2020) synthesized SrSnO 3 with ZrO 2 as a supporting semiconductor for photocatalytic degradation of a textile azo dye pollutant. Honorio discovered from SEM analysis that SrSnO 3 was uniformly dispersed on ZrO 2 which infers higher activity as a result of SrSnO 3 active phase even in a smaller amount.…”
Section: Tantalum and Other Perovskite-based Materials In Photocatalysismentioning
confidence: 99%
“…The mechanism, as investigated by Honorio et al [49] and Ong et al [50], is related to the interaction of the reactions described in the equations below (Equations ( 10)-( 20)). To summarize, it is possible that photogenerated electrons could react with O 2 to generate the anionic radical O •− 2 of superoxide and eventually the hydroxyl radical OH • .…”
Section: Photocatalytic Activation and Potential Mechanismmentioning
confidence: 99%